Hak Imunitas Advokat terhadap Pembelaan Klien - Nur Dalilah Harahap; Nabila Yasmine Al Khanis; Fauziah Lubis (Fakultas Syariah IAIN Laa Roiba Bogor, 2023)
Advocates are professionals who provide legal services both on and off the court as required by the provisions by this law. Pasal 16 about Law of Advocat stipulates of a lawyer can't to forcessed because he is doing his job, namely defending his client during the judicial process. If there is bad faith from the Advocate, then the Advocate's right to immunity or legal immunity does not apply. In other words, Advocates' right of immunity is not given absolutely. This is because the Advocate profession is not only law enforcement, but also a legal profession that provides legal services and services based on legal skills. Problems between individuals and groups are often unavoidable in people's lives, problems that often occur and cannot be avoided include legal disputes. These legal disputes sometimes cannot be resolved by the parties themselves through deliberation to reach a consensus so that in the end they have to be processed through legal channels (court proceedings). If a dispute must be resolved legally, all circles need professional services in the legal field to help resolve the legal dispute. According to the description of the background problem, Many problems can be formulated and solved scientifically in this research . Some of these among the several conflicts, namely: 1. How about application of advocate immunity rights in Indonesia? 2. What obstacle do advocates experience in implementing rights? immunity in Indonesia and how to solve it? Keywords; Immunity, Advocate, Client Defense.